Factors affecting continuance intention in e-wallet use in Indonesia after COVID-19 - Handayani, Nia; Ariyanti, Maya (Indonesian Journal of Multidisciplinary Science, 2024)
The purpose of this research is to provide input regarding key factors that need to be considered in the nuances of intentions to develop various features on e-wallet applications or platforms in Indonesia so that development companies can compete with similar platforms. Data collection in this research was through distributing questionnaires online using Google Form. Respondents in this study totaled 275 respondents who were e-wallet users. The analysis technique used is the Structural Equation Model (SEM) using the SmartPLS4 application. The results of data processing show that Attitude is the factor that most influences Continuance Intention with a t score of 3.682 > 1.96, p-value 0.05 and original sample 0.268, followed by the Habit factor t-statistic value 3.655 > 1.96, p-value 0.05 and original sample 0.29. Meanwhile, the variables that influence Continuance Intention through Attitude mediation are Perceived Usefulness, Perceived Ease of Use and Satisfaction. E-wallet service providers should strategize platforms with loyalty programs, provide after-sales service, understand user expectations, and involve users in service design to increase satisfaction.